Development of the Malaysian Folklore Heritage Game - Yan Peng, Lim; Hui Xian, Wong (2008)
The aim of the paper is to encourage Digital Media Department students of Faculty of Creative Multimedia, Multimedia University, Malaysia learn about Malaysian folklore through the exploration of game teaser. Students were assigned a project on creating a game teaser to introduce the different folklores. The goal is to encourage students to think creatively based on their interpretation, imagination and, expression of the folklore. Front the project research, students would be able to improve their knowledge and recognize the value of Malaysian culture. This paper discusses the process of developing the game towards increasing a significant understanding of the local cultural heritage.